Can Natural Products Suppress Resistant Helicobacter pylori to Fight Against Gastric Diseases in Humans?. Issue 1 (19th February 2020) - Wang, Li‐Shu; Echeveste, Carla Elena; Yu, Jianhua; Huang, Yi‐Wen; Lechner, John; Mei, Ling; Sanvanson, Patrick; Yearsley, Martha; Wang, Chin‐Kun; Stoner, Gary
Abstract : More than 50% of the world's population is infected with Helicobacter pylori . H. pylori is the major causative agent of gastric ulcers and gastric cancer. H. pylori eradication using antibiotics either alone or together with a proton pump inhibitor is the primary strategy to decrease the incidence of gastric cancer. Although eradication therapy is effective, there are significant adverse effects and more importantly, resistance to antibiotics occurs, which represents a major therapeutic challenge. Multiple natural products have been shown to suppress H. pylori both in vitro and in animal model systems. However, only a handful of natural products have been evaluated in human clinical trials. The focus of this review is to summarize the results of published human clinical trials to assess the ability of natural products to reduce or eliminate H. pylori infections. Current evidence suggests that these products appear to have great potential to be developed as pharmaceutical candidates for eradication of H. pylori, hopefully both antibiotic‐sensitive and antibiotic‐resistant strains. Frequent consumption of locally produced foodstuff for controlling H. pylori infection in different countries around the world may well be a feasible long‐term solution to fight against this worldwide prevalent pathogen.